Pelatihan Penyusunan Asesmen Keterampilan Proses Sains Bagi Guru IPA di Kecamatan Saparua dan Saparua Timur - Elsina Sarah Tamaela; Altje Latununuwe; Estevanus K Huliselan; Sarlota Singerin; Juliana Nirahua; Anatasija Limba; Heppy Sapulete; Asry N Latupeirissa; Seska Malawau; Aditya Kainama; Claudya Sabono (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2026)
The implementation of training on preparing Science Process Skills (KPS) assessments for science teachers in Saparua and East Saparua was motivated by the low literacy and numeracy achievements recorded over the past three years. One of the strategic efforts to improve these competencies is through the integration of KPS in science learning, which requires teachers to design appropriate and effective assessments. This community service program (PKM) was conducted through three main stages, namely preparation, implementation, and evaluation. During the preparation stage, observations and interviews were carried out with school principals and education area coordinators in Saparua and East Saparua Districts to identify teacher needs and technical requirements. The training activities were held at SMPN 16 Central Maluku in Waisisil Village with 27 participants and SMPN 28 Central Maluku in Tuhaha Village with 22 participants. The implementation stage began with a pre-test followed by material delivery and practical training sessions. The post-test results showed that participants’ average understanding reached 67.85 in Saparua and 68.38 in East Saparua. The gain test analysis in Saparua indicated that 37% of participants were in the low improvement category, 26% in the medium category, 15% in the high category, and 22% experienced a decline. In East Saparua, 36% were in the medium category, 27% in the low category, 14% in the high category, and 23% showed no improvement. Overall, the training successfully enhanced teachers’ understanding and skills in developing KPS-based assessments.